CHALLENGES AND PERSPECTIVES OF HEALTH EDUCATION IN THE TRANSITION FROM A HOSPITAL-CENTRIC MODEL TO HEALTH PROMOTION - Mazi, Sara Gabriela Josiane; dos Santos, Maria Rita Alves; Francelino, Jéssica da Silva; Costa, Adriana Garcia; da Silva, Isléia Nonis; Custódio, Flávia Cristina; da Silva, Fabricio Sidnei; Franco, Rauer Ferreira (Seven Editora, 2026)
This bibliographic review analyzes the transition from the hospital-centered (biomedical) model to the Health Promotion paradigm, focusing on the strategic role of Health Education in this process. The traditional biomedical model is criticized for its reductionist, fragmented, and financially unsustainable nature, especially in the face of the rise of chronic diseases. Health Education is presented as a central tool for this change, encompassing both traditional behavior-change approaches and emancipatory perspectives grounded in Paulo Freire. Multiple barriers to effective implementation are identified: professionals' intrapersonal beliefs, gaps in academic training, institutional resistance, systemic focus on curative care, and low community health literacy. Regarding future perspectives, the Astana Declaration (WHO), the "Health in All Policies" concept, innovative comprehensive care models such as the Two-Circle Model, and the integration of digital technologies (artificial intelligence, wearables, genomics, telehealth) stand out. The conclusion is that the effective transition requires coordinated efforts in curriculum reform, resource allocation, professional training, health literacy promotion, and ethical integration of digital technologies.